Establishment of a strategy of circular economy increasing the well-being of society: comparison of two national policies; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Kaliuzhniy B. Boris (2016, 2016)
Title screen